Evaluation of metformin versus insulin in the management of gestational diabetes mellitus: a prospective comparative study - Munshi, Shabana; Khandaker, Shamim (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objectives of current study were to assess the efficacy of metformin in the management of Gestational Diabetes Mellitus (GDM) and to compare maternal fetal outcome between metformin and insulin in GDM. Methods: It is a prospective comparative study performed in a tertiary centre. 100 women diagnosed with gestational diabetes mellitus according to Diabetes in Pregnancy Study group of India (DIPSI) criteria at booking and/or between 24-28 weeks of gestation.These women were divided randomly into two groups, 50 patients in each group and they are subjected to pharmacological treatment with either insulin or metformin. Optimum glycemic control between the two groups is studied along with maternal and fetal outcome. Results: Our study to showed no significant difference in GDM with the use of metformin or insulin (P = 0.15). 84% of insulin group had good glycemic control whereas in metformin group, 72%, achieved euglycemic state. Maternal and fetal outcome are also comparable between the two groups. Conclusions: In GDM, glycaemic control can be done a combination of MNT (medical nutrition therapy), exercise and using the oral drug metformin without risk of teratogenicity or maternal hypoglycemia and with comparable neonatal outcome.